Technology of cachaca - Costa, Gustavo Henrique Gravatim; Teixeira, Vitor [UNESP]; Silva, Aline Ferreira [UNESP] (My University, 2021)
This chapter shows the technology of cachaca production. Cachaca is a Brazilian spirit beverage that is obtained from distillation of sugarcane juice fermented by yeast. The beverage has been produced in Brazil for over 400 years and, in the last 20 years, it has also been consumed in Europe and North America. We show the parameters that may influence the chemical and sensory quality characteristics of this beverage, approaching the raw material, the juice extraction and its treatment, fermentation process, distillation and Brazilian regulations.
Keywords: Brazilian beverage; Spirit; Sugarcane